2021
DOI: 10.1097/hrp.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aggression in Adults with Autism Spectrum Disorder: A Review

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by markedly impaired social interaction, impaired communication, and restricted/repetitive patterns of behavior, interests, and activities. In addition to challenges caused by core symptoms, maladaptive behaviors such as aggression can be associated with ASD and can further disrupt functioning and quality of life. For adults with ASD, these behaviors can portend adverse outcomes (e.g., harm to others or to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 180 publications
0
19
0
2
Order By: Relevance
“…Descriptive information is determined based on a review of each domain receiving a code of “low,” “high,” or “unclear” risk of bias. The SCD RoB tool has recently been applied to meta‐analyses including SCD studies across the fields of education (e.g., Martinez et al, 2021), psychology (Davis et al, 2019), and psychiatry (e.g., Im, 2021). Results for our risk of bias assessment for SCD studies are presented in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive information is determined based on a review of each domain receiving a code of “low,” “high,” or “unclear” risk of bias. The SCD RoB tool has recently been applied to meta‐analyses including SCD studies across the fields of education (e.g., Martinez et al, 2021), psychology (Davis et al, 2019), and psychiatry (e.g., Im, 2021). Results for our risk of bias assessment for SCD studies are presented in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Aggression in persons with IDD and ASD may be learned behavior, have a medical etiology, or stem from a psychiatric disorder (Antonacci et al, 2008; Im, 2021). Theories of causation are the foundation of treatment methodology which in the case of aggression is dominated by behavioral, pharmacological, and combined behavioral-pharmacological interventions (Matson & Dempsey, 2008; Poling et al, 2017).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…From an extensive review of the research literature on treating aggression in adults with ASD, Im (2021) concluded that clinicians should begin with functional assessment followed by assessment-informed behavioral interventions and environmental modifications as necessary. If treatment is not successful, “or if the acuity of the individual’s aggression is too high to permit safe and effective implementation of these approaches” (p. 74), pharmacotherapy should be initiated at the lowest dose possible to produce therapeutic and avoid adverse effects.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Aripiprazole and risperidone are the only two drugs approved by the United States Food and Drug Administration5 6 for children with ASD, specifically to treat irritability. However, their limited efficacy, rates of adverse events and lack of benefits for core symptoms of ASD7 8 raise non-pharmacological interventions as a promising alternative with a broader potential.…”
Section: Introductionmentioning
confidence: 99%